Design students meet industry players: Feedback and creativity in communities of practice - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando (My University, 2020)
This work investigates the social collaboration and creative outcomes of teams of learners in Higher Education (HE) Design studies, in the context of cross-organizational (university/industry) Communities of Practice (CoP). These refer to groups of people who share a common interest in a field and connect to co-create knowledge. The study focuses on the feedback delivered by the industrial members of the CoP through collaboration technologies, to complement academic feedback. Findings have shown a twofold effect on learners. On the one hand, critical feedback on the deliverables increased both the time-pressure and the complexity of the work, affecting the teams’ perception of their performances. On the other hand, feedback appeared to inspire better creative outcomes while improving the teams’ metacognitive activity and learning regulation. Furthermore, it enabled learners to pragmatically realize their status within the broader geography of professional practice and reconfigure their achievement goals accordingly. These findings confirm the contribution of cross-organizational CoPs in HE and are discussed with reference to the CoP theory and modes of belonging,as fundamental for learning and identity evolution.
Keywords: Communities of practice; Feedback; Creativity; Collaboration; Design education; Collaboration technologies